Kingship and memory in ancient Judah - Wilson, Ian Douglas (Oxford University Press USA - OSO, 2017)
Kingship and Memory in Ancient Judah investigates kingship in Judean discourse, particularly in the early Second Temple era. In doing so, it contributes to our knowledge of literature and literary culture in ancient Judah and also makes a significant contribution to questions of history and historiographical method in biblical studies.